As 5G Mobile Private Security Analysis Based on Cloud Computing - Michelle Octavia Yolanda Sari (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
As time passes by, the increasing demands from 4G technology services to 5G technology are getting bigger. In line with the development of 5G, there are several open sources such as Free5gc, Open5gs which already provide core 5G network services so that they can help create and simulate private 5G networks. By using free5gc open source, it still needs more attention from the security side, especially from common attacks such as DDoS. Then the attack scenario is carried out from the inner network side, namely from the UE with the TCP SYN Flood and Ping of Death attack methods. The results of the attack contained comparisons for CPU and memory usage parameters. Then the TCP SYN Flood attack had an impact on the core network function components, namely Access and Mobility Management (AMF), which in 5G services experienced errors or crashes after receiving large packets. Thus, users cannot use the service because if an error occurs in the core network function (AMF), then the connection to gNB and the UE will also be lost